Robust extimation of scale of an exponential distribution - Ursula Gather; Verena Schultze (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1997)
We consider a new estimator of scale for exponential samples which is most B-robust in the sense of Hampel et al. (1986). This estimator is compared with two other estimators which were proposed by Rousseeuw and Croux (1993) but for a Gaussian model. All three estimators have the same breakdown point, but their explosion bias curves are different. It is shown that under a gross error model the explosion bias curve of the new estimator performs better than the bias curves of the other estimators.
Keywords: 519; Influence function; breakdown point; explosion bias curve